(untitled) (Revista de Ciências Agroveterinárias, 2020)
Grain quality is essential in the food industry, and it shows variations depending on crop management conditions in the field. The objective of this study was to quantify the effect of hybrids, sowing seasons, and topdressing nitrogen rates on the incidence of damaged grains and their correlation with pathogenic fungi. The experiment was conducted under field conditions in Atalanta, Santa Catarina, Brazil, in a split split-plot randomized block design consisting of the AG9025 PRO3 (super-early) and 30F53 VYH (early) hybrids, preferential (September 20) and late (December 5) sowing season, and nitrogen rates (0, 150, 300, and 450 kg ha-1). The percentage of normal, fermented, and burned grains, as well as the incidence of fungi in grains, were quantified. The hybrid 30F53 VYH had shown the lowest percentage of fermented grains (8.4%) when compared to the hybrid AG9025 PRO3 (43.2%). No significant difference was observed between the sowing season for fermented grains. The hybrid AG9025 PRO3 had shown an increase in fermented grains with nitrogen addition, while the hybrid 30F53 VYH presented a stable behavior. The hybrid AG9025 PRO3 (35.5%) showed the lowest incidence of Fusarium verticillioides in the grains when compared to the hybrid 30F53 VYH (49.9%). The fungus incidence was also lower in the preferential sowing season (35.7%) than in the late one (49.7%). The hybrid AG9025 PRO3 maintained the percentage of fungus incidence stable as a function of nitrogen rates. No significant correlation was observed between the percentage of normal and fermented grains with the incidence of F. verticillioides.